Technical efficiency of wheat growers in some selected sites of Dinajpur District of Bangladesh - Kamruzzaman, M; Islam, Mohammad Hedayetul (Bangladesh Journal of Agricultural Research, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The present study was undertaken to find out the technical efficiency and factors affecting inefficiency of wheat production in Dinajpur District of Bangladesh. The data were collected from 01 July to 30 September 2004. The range of technical efficiency varies from 40% to 99% and the average was 70.33%. Farmers with optimum sowing and optimum harvest were technically more efficient than the farmers with late sowing. In all farms technical efficiency was much higher for the farmers who use sandy loam soil for wheat production than the farmers who did not use sandy loam soil. There was a positive relationship between the educational level and technical efficiency of wheat practicing farmers. The farmers who contacted frequently with extension workers were technically more efficient than who contacted less with extension workers. Therefore, maintaining of optimum sowing and harvesting time, use of sandy loam soil, high level of farming experience and education are important factors for obtaining maximum achievable yield. Key Words: Technical efficiency, wheat growers, optimum sowing and harvest. doi:10.3329/bjar.v33i3.1595 Bangladesh J. Agril. Res. 33(3) : 363-373, September 2008